Characteristics of Seawater and Sediment in Coastal Areas of Ninh Thuan - Pham, Huu Tam (H. : ĐHQGHN, 2019)
This paper represents some aspects of the environmental quality of coastal areas in Ninh Thuan province. Results of two surveys (performed in July 2013, and February 2014) showed that in the water environment, Dissolved Oxygen– DO values were relatively high (always >5mg/l). Values of Total Suspended Solids - TSS, nutrients amoni, nitrite, nitrate, phosphate, silicate and heavy metals Pb, Hg, As were in the narrow ranges and always were lower than acceptable values for aquatic life protection. In general, values of nutrients amoni, nitrite, nitrate và phosphate were usually lower in Nha Trang bay but higher in the coastal area of Phu Yen. In July 2013, values of TSS, nutrients nitrate, silicate were higher than those in February 2014, while Hg was contrary. In sediment, concentrations of organic Carbon were suitable for benthos. Concentrations of Phosphorus and Nitrogen in samples were not high so it does not affect aquatic life. In general, the quality of the sediment in Ninh Hai was better than that of the Ninh Phuoc. Concentrations of Phosphorus and Nitrogen in sediment were higher in February 2014